"To Thrill You, I'll Use Any Device': An Interview with Queen founder members Brian May and Roger Taylor. (26th October 2021) - Winkler, Ray
Abstract: What about the bands that grace STUFISH stages – the clients of entertainment architecture? In an intimate and exclusive interview with Queen founder members Brian May and Roger Taylor, Guest‐Editor of this AD issue and STUFISH Design Director Ray Winkler explores their perspectives on gigging, past and present. Much has changed over the course of the rock group's more than 50‐year history, from the theatrical nature of performances to the technology, sound and visuals. They offer their thoughts on it all.